Horton hears a Who! - Seuss, Dr. (London : Harper Collins Children's Books, 2004)
Horton the elephant goes to great trouble to protect some very small creatures who make their home on a speck of dust.
Booklist.
Library Journal.
Wilson's Children.
3.8.
3.8
K-3
Keywords: Elephants -- Juvenile fiction; Nonsense verses; Elephants -- Fiction; Nonsense verses; Elephants -- Fiction; Nonsense verses